2 - Dating Practices and Patterns of Disclosure among in-School Adolescents in Oyo State, Nigeria - Melvin, Agunbiade Ojo (Africa Development, 2021)
Dating relationships are central to adolescents’ lives. Dating and romance are major topics of adolescents’ conversations and are linked to both positive and negative emotions. This study examined dating patterns, dating disclosure and parent’s awareness in Ibadan metropolis using a mixed method design and found that adolescents are confronted with cultural, religious, situational and self-imposed dilemmas in negotiating the boundaries between privacy and disclosure. Previous unsolicited sexual experiences and the media were influential in facilitating dating intentions. Gender and age were dominant factors in the disclosure and dating patterns of the adolescents with more females than males involved in dating, and older adolescents (ages 17-19) disclosing more about their dating relationships to peers than those between 14 and 16 years of age. This research also established that when parents were suspicious of their adolescents’ involvement in dating because parents were apprehensive of adolescents’ ability to manage dating relationships, most adolescents distorted the information they divulged.